Ethics and Values in Social Work - Banks, Sarah (Basingstoke : Macmillan, 1995)
This book combines a sound grasp of theoretical issues with a clear focus on policy and practice in the 1990s. It will be of use to students, teachers and practitioners.
Includes bibliographical references (p. 166-176) and index.
Keywords: Social Service -- Moral and Ethical Aspects; Social ethics; Social values; Society